Percolaton effects in nanostructured thin films - King, Paul J. (Trinity College (Dublin, Ireland). School of Physics, 2013)
Typically, materials with high electrical conductivity such as metals are opaque, and materials with high optical transparency such as glass are insulating. Finding materials that are both transparent to visible light and electrically conductive has proven to be a significant challenge. There is an ever increasing need for such materials as many of today's popular electronic devices require one or more layers to be both transparent while simultaneously applying a voltage or conducting a current. Indium tin oxide (ITO) is by far the most common material as it satisfies industry requirements for most devices. However, it has several critical drawbacks (for example, brittleness, high cost and being typically deposited via sputtering under vacuum). In recent years solution processed nanomaterials have emerged as a potential alternative. These materials can be deposited over large areas at low temperatures, greatly increasing yield and throughput and reducing cost, while the nanomaterial topology enables flexible devices.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin